Acceptance of non-muslim customers on Bank Islam Malaysia Berhad (BIMB) products and services / Muhammad Yahya Shafee - Shafee, Muhammad Yahya (2012)
This paper analyses the effect of profit and service charges, service quality, convenience and management with the acceptance of non-Muslim customers on Bank Islam Malaysia Berhad (BIMB) products and services. As we can see nowadays, Islamic banking sectors have rapidly growing over the period of time. This is due to the acceptance of non-Muslim people all over the world on the Islamic banking products and services provided by the institutions. This study is concerning on the non-Muslim customers that using products and services of BIMB. 250 structured questionnaires were administered in 2012. Overall, the results of this research show that profit and service charges, service quality, convenience and management showedthe relationship with the acceptance of non-Muslim customers on BIMB products and services.